'TIP OF THE TONGUE' IN THE UTTERANCES OF INDONESIAN FOREIGN SPEAKERS: CASE STUDY OF BIPA STUDENTS ('TIP OF THE TONGUE' DALAM UJARAN PENUTUR ASING BAHASA INDONESIA: STUDI KASUS MAHASISWA BIPA) - Fida Pangesti; Arti Prihatini (Leksema: Jurnal Bahasa dan Sastra, 2020)
Tip of the tongue (ToT) is experienced by BIPA students when speaking Indonesian due to delayed lexical access. This study aims to describe two focuses, namely: (1) the characteristics of the target vocabulary and the ToT vocabulary and (2) the mental processes when the ToT occurs. The theory used in this research is lexical retrieval in morphosemantics. This research method is descriptive qualitative. Data collection was carried out by observation and interview techniques during the learning process of BIPA Muhammadiyah Malang University. The results showed that ToT occurred in nouns (42%), verbs (24%), adjectives (21%), conjunctions (8%), and numeralia (5%). Tip of the tongue is accompanied by a lot of silence as a fallacy effect that appears in the speech. Gestur becomes a description of the meaning features of the target vocabulary. The mental process of ToT occurs in several events, namely (1) the speaker has a picture of the object in his mind, (2) the activation of the semantic set when the active vocabulary has a relation with the meaning of the target vocabulary, (3) activation of the meaning field when the speaker describes it, (4) activation of the phonological set when the similar sound vocabulary appears in the mind, and (5) the appearance of the first language and / or intermediate language.